Does the Advent of Federal Democracy and Madheshi Movement Significantly Successful to alter the Lives of Madheshi Dalit ? (A Study of Inaruwa Municipality, Sunsari District) (Voice of Teacher, 2022)
The Madheshi Dalits of Nepal fall below the national average for human development. They are also denied from basic human rights. In this article, researcher has examined the socio economic situation of Madheshi Dalits of eastern Tarai after Madesh movement and the country of Nepal attained Federal Democracy. The study is founded on a design for qualitative and quantitative research. It is conducted in Inarwa Municipality ward no 9 and sample of Dalit people, Dom, Khatwe, Paswan, Mushahar, and Chamar people is used. Interview schedule, observation, and case study methods have been used in the process of data collection. Data descriptively evaluated and has presented using basic statistical methods. The study has reached in conclusion that social and economic exclusion, inequality, and caste-based discrimination, illiteracy are equally significant contributors to the underdevelopment and poverty in the Madheshi Dalit community. The Madheshi caste-based Hindu hierarchical culture and prejudice are also significant among them. According to the study, the advent of federal democracy and Madhesh movement in Nepal did not significantly alter the lives of the Dalit community. Still prevalent are societal injustices like poverty, unemployment, discrimination, and violence. Increased in political engagement of Dalit activists have all had a significant impact on the study area's Dalit population. They know very little about Dalit's political rights and freedoms, as well as Dalit representation in local government. They have started to speak out about equal representation of man and women in local government and against many forms of social prejudice and violence both within and outside the group.